Incompatibilities of Using the IFRS Fair Value Basis in the Iranian Banking Business Framework - Elias Badri; Ahmad Badri (Iranian Journal of Accounting, Auditing & Finance)
Fair value is one of the primary measurement basis in IFRS, especially for financial instruments. Since this measurement basis is derived from market logic, it can only work correctly if the business of the financial reporting unit is also consistent with this logic. The Banking business model as a financial intermediary is attracting resources and allocating them to resource applicants. This study investigates the compatibility of Iranian banking business with the fair value measurement logic described in IFRS. Our research methodology includes; a systematic review of IFRS Standards, literature, global experiences of implementing fair value, and a questionnaire (including 4 topics and 28 questions). We sent the questionnaire to four groups of respondents, including banks, Independent auditors of banks, supervisory institutions, academic experts and researchers, to collect Professional perspectives and opinions. Finally, we analyzed responses to our questionnaire (with a 90% rate of return) using a fuzzy logic method. Findings indicate that the banking business framework in Iran is influenced by three main factors: legal, policy, and managerial structure. Each of these factors imposes restrictions on the banking business, creating a deep gap between market logic and what runs in Iran’s banking business. Therefore, the possibility and quality of fair value implementation in the financial reporting of Iran's banking industry will depend on when and how to fill this gap.